2022
DOI: 10.1002/jcop.22815
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and risk of retraumatization in adults with a past exposure to potentially traumatic events: A cross‐cultural exploration across Egypt, Germany, and Italy

Abstract: Aims This study aims to: (1) explore the links between past exposure to potentially traumatic events, fear of contracting COVID‐19 and perceived stress; (2) investigate how the exposure to traumagenic experiences affects one's locus of control over their health; and (3) examine fear, stress reactions and differences in health locus of control across three different sociocultural contexts. Methods A total of 524 adult participants were recruited from Egypt, Germany, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…As an example, Welfare-Wilson et al [41] reported on their own psychological distress from wearing masks as survivors of IPV, as it served as a physical reminder of the abuse they had endured. Fishere et al [42] examined populations in Egypt, Germany, and Italy with a history of trauma and determined that those who had experienced trauma were more at risk for the negative mental health impacts of the pandemic than participants without past exposure to trauma (most instances of IPV would be considered traumatic by those experiencing them). Often, social isolation is a tactic perpetrators of violence use to separate victims from resources, family, and friends and may be re-experienced by survivors when their government directs them to self-isolate [43].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, Welfare-Wilson et al [41] reported on their own psychological distress from wearing masks as survivors of IPV, as it served as a physical reminder of the abuse they had endured. Fishere et al [42] examined populations in Egypt, Germany, and Italy with a history of trauma and determined that those who had experienced trauma were more at risk for the negative mental health impacts of the pandemic than participants without past exposure to trauma (most instances of IPV would be considered traumatic by those experiencing them). Often, social isolation is a tactic perpetrators of violence use to separate victims from resources, family, and friends and may be re-experienced by survivors when their government directs them to self-isolate [43].…”
Section: Introductionmentioning
confidence: 99%
“…Fishere & Bartoli's ( 2022 ) article titled “ COVID‐19 and Risk of Retraumatization in Adults with a Past Exposure to Potentially Traumatic Events: A Cross‐cultural Exploration across Egypt, Germany, and Italy ” explored the links between past exposure to potentially traumatic events, fear of contracting COVID‐19, and perceived stress that impacted a sample of adults in Egypt, Germany, and Italy. The authors also explored how exposure to traumagenic experiences affected locus of control over the health of the sample.…”
mentioning
confidence: 99%